Fumigation Using 1,3-Dichloropropene Manages Meloidogyne enterolobii in Sweetpotato More Effectively than Fluorinated Nematicides - Grabau, Zane J (Plant disease, 2024)
Meloidogyne enterolobii is an emerging global threat and is damaging to sweetpotato (Ipomoea batatas) production in the southeast United States. Nematicide application is one of the few management strategies currently available against this nematode, and field testing is urgently needed. The objective of this study was to assess common nematicides for management of M. enterolobii and nontarget effects on free-living nematodes in sweetpotato field production. Treatments were (i) untreated control, (ii) fumigation using 1,3-dichloropropene, or at-transplant drench of fluorinated nematicides (iii) fluazaindolizine, (iv) fluopyram, or (v, vi) fluensulfone at 2 or 4 kg a.i./ha. In 2022, a field trial was conducted under severe M. enterolobii pressure and was repeated in 2023 in the same location without treatment rerandomization. Fumigation using 1,3-dichloropropene (1,3-D) was the only consistently effective nematicide at improving marketable yield relative to control and also consistently reduced most storage root galling measurements and midseason Meloidogyne soil abundances. Fluensulfone at 4 kg a.i./ha consistently improved total yield but not marketable yield, whereas fluensulfone at 2 kg a.i./ha, fluazaindolizine, and fluopyram did not improve yield. Each fluorinated nematicide treatment reduced at least one nematode symptom or nematode soil abundances relative to control, but none provided consistent benefits across years. Even with 1,3-D fumigation, yield was poor, and none of the nematicide treatments provided a significant return on investment relative to forgoing nematicide application. There were minimal effects on free-living nematodes. In summary, 1,3-D is an effective nematicide for M. enterolobii management, but additional management will be needed under severe M. enterolobii pressure